Pelatihan Konseling Kognitif Perilaku Budaya Madura bagi Guru Bimbingan dan Konseling - Hidayah, Nur; Ramli, M.; AT, Andi Mappiare; Fauzan, Lutfi; Hanafi, Husni (Universitas Negeri Malang, 2023)
This community service is the application of the results of research on the development of Madura's Cognitive Behavioral cultural counseling model that is encompassed in the paradigm of cognitive behavioral counseling based on local wisdom in East Java. The training was carried out through expository activities, discussions, and practices through peer-counseling in the implementation of the Madurese cultural cognitive behavior counseling model. Madurese cultural cognitive behavior counseling model Training has a goal that is intended for junior high school counselors in Malang City and the Madura region, which specifically guides students with Madurese cultural backgrounds in their schools. The outcome of community service is to increase the cognitive behavioral counseling skills of Madurese cultural behavior of the counselors who guide students with Madurese cultural backgrounds in Malang City and the Madura region.Pengabdian pada masyarakat ini merupakan penerapan hasil penelitian tentang pengembangan model konseling Kognitif Perilaku budaya Madura yang terangkup dalam paradigma konseling kognitif perilaku berbasis kearifan lokal Jawa Timur. Pelatihan dilakukan melalui kegiatan ekspositori, diskusi, praktik melalui peer-counseling dalam pelaksanaan model konseling Kognitif Perilaku budaya Madura. Pelatihan keterampilan konseling Kognitif Perilaku budaya Madura ini memiliki sasaran yakni diperuntukkan kepada para konselor SMP di Kota Malang dan wilayah Madura, yang khususnya membimbing siswa berlatar budaya Madura di sekolahnya. Hasil yang ingin dicapai dari pengabdian pada masyarakat ini adalah meningkatnya keterampilan konseling kognitif perilaku budaya Madura para konselor yang membimbing siswa berlatar budaya Madura di Kota Malang dan wilayah Madura.